Pathways of change : grammaticalization in English - Fischer, Olga; Rosenbach, Anette; Stein, Dieter, 1946- (Studies in language companion series ;, 2000)
There is a continual growth of interest among linguists of all-theoretical denominations in grammaticalization, a concept central to many linguistic (change) theories. However, the discussion of grammaticalization processes has often suffered from a shortage of concrete empirical studies from one of the best-documented languages in the world, English. Pathways of Change contains discussion of new data and provides theoretical lead articles based on these data that will help sharpen the theoretical aspects involved, such as the definition and the logical connection of the component processes of.